Cucumber Anthracnose in Florida - Jessica Palenchar; Danielle D. Treadwell; Lawrence E. Datnoff; Amanda J. Gevens (EDIS, 2009)
PP266, a 5-page illustrated fact sheet by Jessica Palenchar, Danielle D. Treadwell, Lawrence E. Datnoff, and Amanda J. Gevens, describes the symptoms, causal organism, disease cycle, and management of cucumber anthracnose in Florida. Includes references. Published by the UF Department of Plant Pathology, May 2009.